APPROACHES TO EDUCATION IN THE CREATIVE ACTIVITY OF EASTERN THINKERS (TAMADDUN NURI JURNALI, 2024)
This article widely covers valuable ideas about approaches to education in the creative activities of Eastern thinkers. The views and ideas put forward by Eastern thinkers in ancient times still serve as spiritual food for the minds and hearts of students as an important educational source.